2011
DOI: 10.1016/j.ejca.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sun exposure and melanoma risk for tumours in different body sites in a large case-control study in a temperate climate

Abstract: Aim A melanoma case-control study was conducted to elucidate the complex relationship between sun exposure and risk. Methods 960 population-ascertained cases, 513 population and 174 sibling controls recruited in England provided detailed sun exposure and phenotype data; a subset provided serum 25-hydroxyvitamin D3 levels. Results Phenotypes associated with a tendency to sunburn and reported sunburn at ≥20 years of age were associated with increased melanoma risk (OR 1.56, 95% CI 1.23-1.99). Holiday sun exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
116
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 100 publications
(134 citation statements)
references
References 23 publications
11
116
1
1
Order By: Relevance
“…In a previous article, the same group reported a statistically significant reduced risk of melanoma associated with recreational sun exposure, in particular with week-end sun exposure. 2 Although these findings are not in agreement with a wealth of data showing increased risk of melanoma associated with recreational sun exposure and sunbed use, particularly when exposures start at younger age, some studies 3,4 found results similar to those found by Elliott et al 1 The main issue we would like to raise is whether this study had an adequate design for investigating associations between melanoma and lifestyle risk factors.…”
Section: Dear Editorcontrasting
confidence: 47%
“…In a previous article, the same group reported a statistically significant reduced risk of melanoma associated with recreational sun exposure, in particular with week-end sun exposure. 2 Although these findings are not in agreement with a wealth of data showing increased risk of melanoma associated with recreational sun exposure and sunbed use, particularly when exposures start at younger age, some studies 3,4 found results similar to those found by Elliott et al 1 The main issue we would like to raise is whether this study had an adequate design for investigating associations between melanoma and lifestyle risk factors.…”
Section: Dear Editorcontrasting
confidence: 47%
“…We also performed some subgroup analyses stratifying by the factors defined by Cust et al (sex, age at diagnosis/interview, sun sensitivity phenotype, nevi, lifetime total sun exposure) and also average number of sunburns during lifetime. In our case-control study, 3 we found the sun exposure measure most associated with risk was a protective effect of regular weekend sun exposure. We therefore repeated the analyses adjusting for this measure but there was no effect on the results (data not shown).…”
mentioning
confidence: 89%
“…A proxy for sun sensitivity phenotype (categorized as sun-sensitive or not sun-sensitive) was derived, as described previously. 3 As far as possible, we repeated the analyses as reported by Cust et al Spearman correlations, Wilcoxon rank-sum tests and Pearson chi-squared tests were performed for pair-wise associations. ORs and 95% CIs were calculated from unconditional logistic regression models using data from cases and population-ascertained controls to assess the sunbed variables as predictors of melanoma.…”
mentioning
confidence: 99%
“…26 An English study published in 2011 showed that regular weekend sun exposure had a protective effect against CMM, and the researchers postulated that this may be mediated by photo-adaptation or higher vitamin D levels. 27 Another point suggested by these studies is that sunburns, and not cumulative sun exposure, lead to increased risk for CMM. In an analysis of 15 casecontrol studies, Chang et al 28 concluded that sunburn is a strong predictor of melanoma at all latitudes, whereas cumulative sun exposure affects melanoma risk only at low latitudes, defined as between 34°north/south and 20°north/south.…”
Section: How Sunscreen Can Contribute To Increased Melanoma Incidencementioning
confidence: 99%